Dumping in competitiveness in clothing companies of the Gamarra commercial emporio, year 2016 - Reyes Trujillo, Elmer (2020)
The objective of this research work is to determine the effects of dumping on the competitiveness of garment apparel companies in the Gamarra Commercial Emporium that began operations in 2016 and determine how dumping affects the company’s growth, positioning and income. It was hypothesized that dumping negatively affects the competitiveness of clothing apparel companies; the deregulation on dumping and the inadequate control that may be exercised for the entry of this type of merchandise, were the causes for some importers to find the opportunity to enter merchandise with dumping prices. The research method was descriptive and explanatory based on the information obtained that allowed us to answer the questions posed. The results show that both variables have a close positive relationship, since a high risk of dumping will generate a low competitiveness. After the investigation it is concluded that the entry into Peru of goods with prices below the price of the similar product in the country of manufacture destined for consumption in the exporting country, negatively affects the business growth of the apparel sector, in the positioning of the internal and external market, as well as in the utility that the company can perceive; Obtaining as result the unemployment of the workers, the reduction in the productive capacity, reduction in the competitive capacity, bankruptcy of the garment companies, closing factories of the affected item, and all this generates an economic instability in our country; Therefore, a greater participation of the State in the regulation and control of this type of products is needed, in order to protect our national industry